PERANCANGAN KURSI AUTISME UNTUK MOBIL SEBAGAI ALAT BANTU TERAPI AUTISME - Naufal, Gostsa Khusnun; Raswan, Awan; Suryo, Sumar Hadi; Jamari, Jamari; Haryanto, Ismoyo (ROTASI, 2013)
Children with autism tend to have hyperactivity, children will tend to be difficult to control. This is certainly an issue when children are in vehicles, especially cars. There are some events related to the automobile accident caused hyperactivity of children with autism. When the children in the car tends to move on, even disturb concentration the driver. Not many safety features on the car is intended for children with autism. Research safety equipment as well as therapeutic tools for children with autism that will be done is a  autism car seat. This tool serves as an extra seat that is able to bind to safely and comfortably seat a child with autism to a primary car seat. This tool is also able to provide autism therapy with the principles of deep pressure when used, generating deep pressure with adjustable pressurized balloon. The tool is attached directly to the car seat with a harness, and then the car safety belt is used as the main security of these devices. Design tools for  autism car seat through stages: preparation of product definition and technical specifications  autism car seat , the design of a product concept for  autism car seat, designing products for  autism car seat , as well as preparation of documents for the manufacture of autism car seats